Inorganic Elemental Composition of Wood of Ficus Religiosa L. (Peepal) - Shrestha, Roshani M.; Dhami, Deependra S. (Journal of Nepal Chemical Society, 2012)
The total ash content and inorganic elemental compositions of the wood of Ficus religiosa L. from Nepal had been studied. The percentage of total ash content were found highest in comparison to other Ficus species. Different eight inorganic elements were detected from wet ash analysis by atomic absorption spectroscopic ( AAS) method. The remarkably high concentrations of K, Ca and Mg were also reported. DOI: http://dx.doi.org/10.3126/jncs.v27i1.6664 J. Nepal Chem. Soc., Vol. 27, 2011 74-77